Accuracy of various activity trackers in estimating steps taken and energy expenditure - Stackpool, Caitlin M. (My University, 2013)
This study was designed to assess the accuracy of various activity trackers in estimating steps taken and energy expenditure. The activity trackers included the Nike Fuelband, Jawbone UP, BodyMedia FIT Core, Adidas MiCoach, Fitbit Ultra, and the NL-2000i. Only the Nike Fuelband, Jawbone UP, FitBit Ultra, and the NL-2000i recorded steps. Twenty subjects (10 males, 10 females) participated in two, 50-minute activity sessions. The first session consisted of treadmill walking and treadmill running. Each exercise was 20 minutes, with a 10 minute break between. The second session consisted of 20 minutes on an elliptical cross-trainer, a 10-minute break, and the time needed to complete the agility drills. The activity trackers were worn concurrently with a portable metabolic gas analyzer. Steps were recorded using a hand counter. At the end of each mini-session, steps and kcals were recorded by each activity device. The results of the study showed steps to be fairly accurate for all devices, but calories to be less accurate. The accuracy of the devices varied depending on the exercise modality. Based on the results, choosing an activity device should be based on the information looking to be recorded and the type of activity to be performed.
Keywords: Exercise tests -- Evaluation.; Energy metabolism.; Exercise -- Physiological aspects.